Health Informatics Education and Research at the University of Athens - Mantas, J. (Yearbook of Medical Informatics, 1998)
In Europe, coordinated activities in healthcare informatics education started in the late 1980s with the establishment of European courses in health telematics. At the same time the European Commission foresaw the need for spreading the knowledge of Information Technology (IT) in the healthcare sector. Therefore the EC, since then, has supported the initiatives that aim to create awareness, stimulate diffusion, and educate and train the users (healthcare professionals) in the application of IT in health care [I] Initiatives, such as the NIGHTINGALE project, are essential for the planning and implementation of strategies for training the nursing profession in using and applying healthcare information systems. Other projects are the IT EDUCTRA project, which is a practical project in the field of education and training of healthcare professionals in information technologies, and the ERASMUS Master’s Course, which aims at giving those working (or intending to work) in the health service and related activities, a broad advanced postgraduate education in health informatics.
Keywords: Education; Health Informatics; Nursing